Transition resistance influence of the upper structure track ballast on the rail-to-earth potential at AC railway sections - A. A. Krylov; I. A. Rebrov; A. V. Rudashevskaya; R. A. Rudashevskiy; E. D. Khar'kovskaya (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The purpose of the research is to evaluate transition resistance modifications of the upper structure track in passing from the ballast to the ballastless track. These modifications effect the rail-to-earth potential difference. Moreover, they refer to the reverse traction system, to the reverse traction current of railway automation devices and to the required level of electrical safety guarantee.Materials and methods. The authors used both the analytical method of the rail-to-earth potential testing and the practical one based on experimental studies of the rail track transition resistance measurements. The authors carried out experiments on the Rozengartovka — Boitsovo — Bikin section of the Far Eastern Railway. This section includes the heavy freight traffic with the increased electric resistance of the track ballast by the upper structure redevelopment.Results. The research defines the main criteria of the rail-to-earth potential considering the 2×25 and 25 kV reverse traction of monophase AC systems with the 50 Hz frequency and depending on the experimental area location in terms of traction substations, on the climate and geological factors and on the freight traffic density.Discussion and conclusion. The obtained results will improve the accuracy of the rail-to-earth potential difference considering not only indicated factors, but also the upper structure type, track features and a feed line scheme for contact wire.